In Contract Law: Unpacking Undue Influence through a Judge's Lens - Dwi Fidhayanti (Journal of Judicial Review, 2023)
This study explores how judges at the Malang District Court view “undue influence”(misbruik van omstandigheden) as a determinant of contractual incapacity in contract law and identifies the criteria they use. Employing an empirical approach with case analysis and sociological perspectives, primary data came from interviews, while secondary data, including court rulings and relevant materials, underwent descriptive and qualitative analysis. The research reveals that cases involving individuals who exploit situations from the beginning of an agreement with malicious intent, strategically using economic and psychological advantages to gain control, are central to the concept of undue influence. Surprisingly, the Malang District Court handles a limited number of such cases, as aggrieved parties often initiate criminal fraud proceedings before filing civil lawsuits citing undue influence. Some rulings categorized undue influence claims as unlawful acts or defaults. In deciding undue influence (misbruik van omstandigheden) cases, judges prioritize two key factors: the substantive content of the lawsuit, pivotal for the court's jurisdiction, and the level of due diligence exercised by parties, considering subject matter, witnesses, and relevant correspondence—all affecting the agreement's validity. Consistency in judicial decisions is recommended to provide legal certainty and predictability for parties involved. This research underscores the need for legal awareness, streamlined procedures, precautionary measures, and ongoing research in this area of contract law